A new species of Silene sect. Dipterosperma (Caryophyllaceae) from Malta - Brullo, Salvatore; Brullo, Cristian; Cambria, Salvatore; Lanfranco, Edwin; Lanfranco, Sandro; Minissale, Pietro; Sciandrello, Saverio; Galdo, Gianpietro Giusso Del (Phytotaxa, 2017)
Silene melitensis, a new species beonging to the sect. Dipterosperma, is described and illustrated from Maltese Archipelago. This therophyte occurs along the calcareous rocky coast of Malta and Gozo islands, where it grows within the ephemeral meadows together with many halophytes. Based on its prostrate-ascending habit and succulent leaves, S. melitensis shows some morphological similarities with S. nummica and S. crassiuscula, both included in the S. colorata group. S. melitensis differs from S. nummica in having inflorescence more flowered, petals smaller, claw on the back pubescent in the midrib, capsule bigger, carpophore shorter and seed with undulate wings, while it differs from S. crassiuscula in having scapes branched at the base, calyx tomentose-hirsute and shorter, petal limb shorter, coronal scales shorter and undulate, ovary shorter and seed larger. An diagnostic key of the taxa belonging to the sect. Dicterosperma is provided.